2023
DOI: 10.1093/ehjcr/ytad162
|View full text |Cite
|
Sign up to set email alerts
|

The great deceiver: a case series of ‘double fire’ atrioventricular nodal response

Abstract: Background The “double fire” (DF) atrioventricular (AV) nodal response is a rare mechanism of two ventricular electrical activations following a single atrial beat due to dual AV node physiology. DF AV nodal response is often misdiagnosed and may lead to unnecessary and sometimes risky interventions. Case summary We describe a series of three cases with distinct clinical manifestations of DF AV nodal response: Patient 1 remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…1 Case series have also shown that the arrhythmia can contribute to tachycardia-induced cardiomyopathy if left untreated. 2,3 Slow pathway modification has been successful in treatment of double-fire tachycardia, with similarly low rates of complications as when used for AV nodal reentry tachycardia ablation. 2 This patient underwent radiofrequency ablation of the slow pathway without complication.…”
Section: Response To Ecg Challengementioning
confidence: 99%
“…1 Case series have also shown that the arrhythmia can contribute to tachycardia-induced cardiomyopathy if left untreated. 2,3 Slow pathway modification has been successful in treatment of double-fire tachycardia, with similarly low rates of complications as when used for AV nodal reentry tachycardia ablation. 2 This patient underwent radiofrequency ablation of the slow pathway without complication.…”
Section: Response To Ecg Challengementioning
confidence: 99%